Representasi Budaya Populer Jepang dalam Komunitas Mirai No Yume di Kota Bukittinggi - Yogi Septia Prayoga; Eka Vidya Putra; Lia Amelia (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2023)
This study aims to explain the representation of Japanese popular culture in the communityMirai No Yume in Bukittinggi City. This research is motivated by the researcher's interest in Japanese popular culture and joining the communityMirai No Yume. Mirai No Yume is a community of young people who love Japanese culture such as:anime, cosplay, manga, and J-Pop in Bukittinggi City. The theory used to analyze this research is the theory of simulacra society put forward by Jean Baudrillard. The research method used for this research is descriptive qualitative research. The selection of informants was carried out by means of purposive sampling with a total of 13 informants. Data collection was carried out by means of observation techniques, interview techniques, and documentation techniques. Then the resulting data is analyzed using data collection techniques, data reduction, data presentation, and drawing conclusions and verification so that the resulting data can be tested for its validity using Miles and Haberman's analysis. The results of the study found that community membersMirai No Yume is a collection of people who are interested in Japanese popular culture in the city of Bukittinggi. Members of the community devote time to collections and devote their passion to Japanese popular culture. CommunityMirai No Yume represent Japanese popular culture by doingcross street, participating in competitions, and participating in events with the theme of Japanese culture. The impact felt by community members since joining the community has positive and negative impacts. People's view of the Japanese community is considered cool because they can express their hobbies.